Global Longitudinal Strain of Chronic Granulocytic Leukemia Patients treated with Imatinib and Nilotinib - Indra Wijaya; Arief Sumarna; Eliza Nurazizah; Evan Susandi; Erwan Martanto (Faculty of Medicine Universitas Padjadjaran, 2021)
Objective: To determine left ventricular function of patients with Chronic Granulocytic Leukemia in Chronic Phase (CGL-CP) who received imatinib and nilotinib by using Global Longitudinal Strain (GLS) examination.Methods: This was a descriptive study involving 46 CGL-CP patients who received imatinib and nilotinib therapy at the Hemato-Oncology Clinic of the Internal Medicine Departement of Dr. Hasan Sadikin General Hospital,, Bandung, Indonesia. Sampling was performed consecutively during the period of October to December 2019. Variables assessed in this study were age, gender, BMI, length of treatment, hemoglobin level, Left Ventricular Ejection Fraction (LVEF) value, and Global Longitudinal Strain (GLS). Primary data were tested for normality using the Saphiro-Wilk test. Statistical analysis was performed using SPSS software version 25.0.Results: Thirty-nine patients (seventeen males and twenty-two females with a mean age of 42±11) who had been in therapy for about 8 to 179 months at the time of the study were included as subjects. On average, the GLS results for both treatment groups indicated a normal value based on the classification of the American Society of Echocardiography. The imatinib group gained a score of -22.4% (average range = -16.4% to (-28.1%)), while the nilotinib group gained a score of -21.6% (average range = -18.0% to (-25.9%)). Conclusion: This study described the left ventricular function based on results of GLS in CGL-CP patients receiving imatinib and nilotinib.